PTH-134 Experiences of using vedolizumab in the treatment of inflammatory bowel disease in the east midlands. (June 2019) - White, JR; Din, S; Ingram, R; Foley, S; Alam, M; Robinson, R; Francis, R; Tucker, E; Jalal, M; Elphick, D; Atallah, E; Norman, A; et al.
Abstract : Introduction: Randomised controlled trials have demonstrated efficacy of vedolizumab in Ulcerative Colitis (UC) and Crohn's Disease (CD). Further data in the real-world setting is needed to inform future practice. Methods: A multicentre retrospective observational chart review study was conducted with all pts initiated on vedolizumab across 7 UK hospitals between 1/11/14–30/11/16. The Health Research Authority approved the protocol (19/HRA/0008). Clinical disease activity was assessed at baseline, week 14, 30 & 52 using the Harvey Bradshaw Index (HBI) and partial Mayo Score (pMS). Clinical remission was defined as HBI≤4 or pMS <2 with a combined stool frequency and rectal bleeding subscore of ≤1. Clinical response was defined as ≥2-point decrease from baseline in pMS and ≥3-point decrease from baseline in HBI. The primary objective was to describe corticosteroid-free and clinical remission. Secondary objectives included effect on disease activity scores, biochemical markers, concomitant drug use, mucosal healing, hospital admissions and adverse effects. Results: 192 patients were included: 100 CD, 87 UC and 5 IBD unclassified (grouped with CD in this analysis). 46% of UC and 10% of CD patients were anti-TNF naïve. Median age was 44 (range 18–79) years; 49% male and median BMI was 25.7 (IQR 22.5–31.4). Exposure time was 38.0 (23.7–56.7) for UC and 30.9 (21.3–49.6) weeks for CD. Corticosteroid-free remission rates for UC and CD were 46% and 45%, while clinical remission rates were 52% and 44% respectively. Clinical response rates for UC was 49% and CD was 53%. The median time to corticosteroid free remission for UC and CD was 17.6 (8.7–29.6) and 14.1 (6.0–21.7) weeks and clinical remission was 15.1 (7.4–24.9) and 10.1 (3.1–21.0) weeks respectively. Time to clinical response for UC was 9.4 (5.7–15.4) and CD was 9.5 (6.1–18.2) weeks. Disease activity decreased from baseline at 14 weeks: pMS 5 (4–6) vs 3 (1–5) p=0.025 and 30 weeks pMS 5 (4–6) vs 2(1–5.5) p=0.032. Concomitant corticosteroid and immunomodulator use decreased in UC (48% vs 15% and 41% vs 18%) and CD (27% vs 10% and 26% vs 7%), respectively. The overall rate of IBD-related hospital admissions per patient per year was 1.3 (0–18.1). Adverse events were reported in 5.2% of patients. Conclusions: Results in our predominately anti-TNF experienced vedolizumab cohort mirror other published real-world data and demonstrate good clinical effectiveness and safety profile.